Wavelet based image denoising using raspberry PI / \c Naseer Abed Ali Raheem - Raheem, Naseer Abed Ali (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2018)
The three objectives studied in this report include ; implement an effective image denoising algorithm with the help of the Python programming language ; analyzing the processing methods by implementing Non-local means and wavelet hard thresholding ; designing a Raspberry Pi-based system for denoising the images.